The TPP and the digital trade agenda: Digital industrial policy and Silicon Valley's influence on new trade agreements - Shamel Azmeh; Christopher Foster (London School of Economics and Political Science (LSE), Department of International Development, 2016)
The global economy is undergoing a digital shift that is likely to intensify with rapid growth in digital trade and digital-based restructuring of economic sectors. While trade in "traditional" goods and services is subject to enforceable rules through multiple agreements, key areas relevant to the digital economy are weakly regulated. This has provided policy space for latecomer economies to implement what we call digital industrial policy. Through denying market access, data localization, and technology transfers, some of the digital industrial policy tools represent a threat to US firms that dominated the digital world and to the position of the US economy as a global digital leader. Consequently, underpinned by growing political power of Silicon Valley, the US adopted the "digital trade agenda" in its trade policy particularly in the so-called 21st century trade agreements; the TPP and TTIP. This trade agenda is likely to expand in the future and will have important implications on digital and economic development.
Keywords: 330; Digital industrial policy; Trans-pacific partnership; data localization; the digital trade agenda; Silicon Valley; digital catching-up